The Influence of Organizational Communication Toward Employee Performance in PT. Pos Indonesia East Jakarta Branch - Suryanto Sosrowidigdo (Journal of Research in Business, Economics, and Education, 2020)
This study aims to prove the effect of organizational communication on employee performance at PT. POS INDONESIA East Jakarta Branch. The method in this study is a quantitative method by taking a sample of 35 respondents. Testing the hypothesis in the study using a simple linear regression analysis. Based on the test results obtained that Ha is accepted which means there is a influence between Organizational Communication and Employee Performance at PT. POS INDONESIA East Jakarta Branch, the magnitude of the influence of Organizational Communication on Employee Performance is very strong at 0.837. The coefficient of determination (r²) in this study shows that organizational communication has an influence of .700 or 70% on employee performance. The results of this study indicate that the independent and dependent variables have a significant and positive effect between organizational communication and employee performance. The higher the organizational communication, the higher the resulting performance, with a linear regression equation Y = 6.116 + 0.841 (X).